(untitled) - Nijensohn, León; Grassi, Carlos J.; Pilasi, Héctor (Universidad Nacional de Cuyo. Facultad de Ciencias Agrarias)

Un procedimiento de campo para medir la intensidad relativa de transpiración (1963)

(untitled)
A method for the determination of the "relative transpiration rate" of leal tissues is proposed. The procedure consists in measuring, simultaneously, the time taken by a cohalt chloride saturated paper to pass from the initial hlue colour to a uniform pink one by the action of disks extracted from leaves and by a water saturated filter paper. This measuring is to be carried out in pecial transpirometrie cameras. The percentual relationship between the time-measured in seconds take by the color shift bzought about by wet filter papel check, with respect to the time taken by the shift in color caused by leaf-disks, is denominated "Index of Relative Transpiration" (IRT) . The final pink color can be appreciated comparing permanent patterns, whose preparation is herein indicated. Two simple models of transpirometric cameras are proposed, hoth suitahle to carry out the determinations in field conditions. The model "A" was used with good results in grapevine, and the "B" model can be employed for any plant and particularly for those whose foliar tissues rapidly lose water by wounds left by the cut and/or during periods of low transpiration rate. I can be deducted form some experiments carried out on grapevine, that with the proposed procedure differences of the transpiration intensities can he brought out in leaves which belong to plants exposed to dif'ferent soil water matric potentials. Experimental examples are given proving that, in the soiI studied the JRT decreases sharply when the available water comes down to less than 50 % of its possible averall availability. The method proposed is being satisfactorily used by the authors in experiments diagnosing time of irrigation.